2020
DOI: 10.26623/philanthropy.v4i2.2188
|View full text |Cite
|
Sign up to set email alerts
|

Pengasuhan Berbasis Kekuatan Karakter Dan Keterlibatan Diri Pada Mahasiswa

Abstract: <p><em>The purpose of this research is to get a correlation between strength-based parenting (SBP) and engagement among college students. The background of this research is the importance of engagement in college. Engagement is known as human adaptive functioning in their life. Engagement is important because it can help college students to direct their efforts and complete assignments seriously. It is necessary to have proper parenting practiced by parents through the application of positive psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…The involvement of all parties in character education is highly crucial to ensure the sustainability and success of this programme as the main pillar of character learning in higher education (Pradana et al 2020). The third stage is building capacity which is carried out by nurturing, learning, mentoring, and consulting which is essential to reinforce student character (Gayatri 2020;Sulastra & Handayani 2020).…”
Section: Character Building Training: Policy and Contentmentioning
confidence: 99%
“…The involvement of all parties in character education is highly crucial to ensure the sustainability and success of this programme as the main pillar of character learning in higher education (Pradana et al 2020). The third stage is building capacity which is carried out by nurturing, learning, mentoring, and consulting which is essential to reinforce student character (Gayatri 2020;Sulastra & Handayani 2020).…”
Section: Character Building Training: Policy and Contentmentioning
confidence: 99%
“…Orangtua dapat memberikan stimulasi melalui bentuk pengasuhan yang tepat. Hasil penelitian menunjukkan bahwa pengasuhan memiliki hubungan dengan keterlibatan anak untuk belajar, kesehatan mental pada anak, kematangan perkembangan anak, dan pencapaian prestasi anak (Jach, Sun, Loton, Chin, & Waters, 2018;Si Han & Pei Jun, 2013;Sulastra & Handayani, 2020;Waters, Loton, & Jach, 2019).…”
Section: Pendahuluanunclassified
“…University students' engagement has been studied by several researchers in Indonesia, including Sholeh (2019), who stated that university students' engagement is still in the low category; Sulastra and Handayani (2020), their research found that university students have high engagement in lectures; research by Qonita, Dahlan, and Damaianti (2021) found that 54.2% of university students had low engagement. This means that the levels of student engagement in several universities still vary.…”
Section: Introductionmentioning
confidence: 99%